2018
DOI: 10.2196/10849
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Universal Prevention for Students and Parents to Prevent Alcohol and Cannabis Use Among Adolescents: Protocol for the Randomized Controlled Trial of Climate Schools Plus

Abstract: BackgroundEarly initiation of alcohol and cannabis use markedly increases the risk of harms associated with use, including the development of substance use and mental health disorders. To interrupt this trajectory, effective prevention during the adolescent period is critical. Despite evidence showing that parents can play a critical role in delaying substance use initiation, the majority of prevention programs focus on adolescents only. Accordingly, the Climate Schools Plus (CSP) program was developed to addr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…Those studies reported the effectiveness of teaching each of the components of social competence in reducing the tendency to use drugs in adolescents and addicts. Also, it is consistent with the results of Chapman et al (2018) who stated that to prevent the early onset of alcohol and marijuana use and reduce their risk, effective prevention in adolescence through increasing awareness of their complications, and related injuries are very important [51].…”
Section: Discussionsupporting
confidence: 89%
“…Those studies reported the effectiveness of teaching each of the components of social competence in reducing the tendency to use drugs in adolescents and addicts. Also, it is consistent with the results of Chapman et al (2018) who stated that to prevent the early onset of alcohol and marijuana use and reduce their risk, effective prevention in adolescence through increasing awareness of their complications, and related injuries are very important [51].…”
Section: Discussionsupporting
confidence: 89%
“…An effect size of 0.2, which is comparable with previous trials of anxiety, depression, and substance use prevention programs [20,21,[31][32][33][34], would have substantial benefits at the population level according to economic modeling [35]. It is anticipated that the majority of students in the year group of participating schools will take part in the study, based on participation rates found in previous school-based trials conducted by the research team [36][37][38][39]. To account for school dropouts during the trial, which are expected to be approximately 10% based on similar previous school-based trials [40], this study will recruit 14 schools (with at least 840 students).…”
Section: Sample Size Calculationsmentioning
confidence: 56%
“…In line with our published protocol ( Newton et al, 2018 ), the primary hypothesis is that the CSP program will be more effective than health education as usual in reducing the rate of increase in alcohol use, heavy episodic drinking and alcohol-related harms among adolescents up to 24 months post-baseline.…”
Section: Introductionmentioning
confidence: 92%
“…The Climate Schools Plus (CSP) combined student and parent program was developed to fill this gap ( Thornton et al, 2018a ). The current study presents the outcomes of a cluster randomized controlled trial (RCT) of the CSP program in Australian secondary schools ( Newton et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%